ANALISIS REKAYASA NILAI PADA PERENCANAAN PROYEK PEMBANGUNAN FASILITAS LABORATORIUM KAWASAN SEKOLAH - Rizal Jaelani; Lioba Evita Anikusuma (STKIP Subang, 2026)
In project construction, cost, quality, and time are key factors that must be optimally managed to ensure the project runs according to plan. One of the common problems encountered in construction projects is the existence of unnecessary costs resulting from inefficient design or material selection. To address this issue, the Value Engineering method can be applied to obtain more economical alternatives without reducing the function and quality of the building. This study aims to analyze wall construction alternatives using the Zero-One method and to determine the cost efficiency achieved through the implementation of Value Engineering in the Construction Project of Supporting Laboratory Facilities for the Vocational School Area.This research employed a quantitative approach using project planning data as the object of analysis. The analysis was conducted by applying the Value Engineering job plan, which consisted of the information phase using Pareto analysis, the function analysis phase using the cost/worth method, the creative phase, the evaluation phase through advantages and disadvantages analysis, the development phase using the Zero-One method, and the recommendation phase. The object of the study was wall construction work, which had significant potential for cost optimization.The results showed that among the six alternatives evaluated, Alternative A2, consisting of a combination of partition walls and 10 cm thick lightweight brick walls, was selected as the best alternative with the highest weight score of 27.11% based on the Zero-One method. The cost of wall construction work using this alternative was IDR 183,032,887.20, which was lower than the existing cost of IDR 196,533,121.75. The implementation of this alternative resulted in a cost saving of IDR 13,500,234.55 or 6.87% of the total wall construction cost.